Empirical Evaluation of the Impact of Development Expenditure on Poverty Alleviation in Nigeria - Wilson, Clement; Akobi, Clement; Babale, Winner Lara (Darul Yasin Al Sys, 2025)
This study investigates the contribution of development financing to poverty alleviation in Nigeria between 1990 and 2023, with a focus on the impact of education and health funding. Time series data were obtained from the Central Bank of Nigeria Statistical Bulletin. The Augmented Dickey–Fuller unit root test indicated that education and health expenditures were stationary at first difference (I(1)), while poverty reduction was stationary at second difference (I(2)). Johansen cointegration results confirmed a long-run relationship among the variables. An Error Correction Model (ECM) was applied to assess the effects of development funding, revealing that government expenditure on education significantly reduces poverty in the long run (p = 0.0225 < 0.05), whereas health expenditure showed no significant short-run impact (p = 0.3210 > 0.05). The results suggest that a 1% increase in education expenditure leads to a 0.0731% reduction in poverty in the short run. The study concludes that development funding can substantially alleviate poverty when resources are efficiently managed and productively invested. It recommends effective implementation strategies and structural reforms in public spending to achieve sustainable poverty reduction in Nigeria.